Shifting perspectives : East German autobiographical narratives before and after the end of the GDR - Tate, Dennis (Studies in German literature, linguistics, and culture., 2007)
Tate provides a detailed account of 'subjective authenticity' in German literature: its origins in the 1930s' exile debates, its evolution during the GDR's lifespan, and its manifestations in the work of five East German authors: Brigitte Reinmann, Franz Fühmann, Stefan Heym, Günter de Bruyn and Christa Wolf.